2022
DOI: 10.1155/2022/4741193
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Summary for Nonpharmacological Management of Chemotherapy‐Induced Nausea and Vomiting

Abstract: Objective. To evaluate and summarize the best evidence for nonpharmacological management of chemotherapy induced nausea and vomiting (CINV). This article aims at serving as a reference for nursing staff to prevent and manage CINV. Methods. We systematically searched for evidence on CINV in databases such as Cnki and Wanfang, guide websites such as GIN and NZGG, and professional websites such as UICC and ACS. Only articles published between November 2012 and November 2021 were considered for inclusion in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…There were many nonpharmacological management measures for CINV, which should be combined with the clinical situation and the patient’s wish, and follow the principle of individuation. [27] By applying the nausea-free ward model in this study, the results showed significant improvement in CINV in chemotherapy patients. This model emphasized multidisciplinary cooperation, continuous identification of deficiencies and improvement of patients’ CINV symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…There were many nonpharmacological management measures for CINV, which should be combined with the clinical situation and the patient’s wish, and follow the principle of individuation. [27] By applying the nausea-free ward model in this study, the results showed significant improvement in CINV in chemotherapy patients. This model emphasized multidisciplinary cooperation, continuous identification of deficiencies and improvement of patients’ CINV symptoms.…”
Section: Discussionmentioning
confidence: 87%
“…One study noted improved outcomes (stress reduction, improved coping, and sleep quality) using an integrative healthcare model that combined heartfulness meditation and care coordination (64). Though lacking data in CVS, studies suggest that acupuncture aimed at P6 or the Neiguan point is safe, improves symptoms in chemotherapy-induced nausea and vomiting, and is used by some patients (65).…”
Section: Review Articlementioning
confidence: 99%